The impact of university teachers’ transformational leadership on students’ social–emotional competence: the mediating role of teacher–student relationship and learning engagement with moderated by self-efficacy - Lin, Lin; Wang, Chunying (Frontiers in Psychology, 2025)
In the context of increasing emphasis on holistic student development in higher education, transformational leadership (TL) demonstrated by university faculty has been linked to positive student outcomes, including social–emotional competence (SEC). This study explored the associations between TL and students’ SEC by examining two potential mediating processes—the quality of teacher–student relationships (TSR) and students’ learning engagement (LE)—as well as the moderating role of self-efficacy (SE). Survey data were collected from 659 undergraduates at multiple universities in China. Using structural equation modeling (SEM) and moderated mediation analysis (PROCESS Model 7), the findings revealed that TL positively influenced students’ SEC through two parallel pathways: by strengthening TSR and enhancing LE. Notably, SE significantly moderated the relationship between TL and TSR, such that the indirect effect of TL on SEC via TSR was stronger among students with higher levels of SE. However, the SE-moderated path via LE was not significant. These results highlight the importance of both relational and motivational processes in leadership-informed pedagogy, and underscore how students’ psychological traits such as self-efficacy condition their responsiveness to instructional leadership. Although the cross-sectional design limits causal inference, this study provides initial empirical support for targeted leadership strategies that align with students’ individual resources to foster social–emotional development in higher education.